War at the Speed of Light : Directed-Energy Weapons and the Future of Twenty-First-Century Warfare - Del Monte, Louis A. (Book collections on Project MUSE., 2021)
""War at the Speed of Light" explores the ever-increasing and revolutionary role of directed-energy weapons in warfare, including laser, microwave, electromagnetic pulse (EMP), and cyberspace weapons. In addition, this book delineates the threat that directed-energy weapons pose to disrupting the doctrine of MAD (Mutually Assured Destruction), which has kept the major powers of the world from engaging in nuclear war"--